Positive quantum dot light emitting diode and preparation method thereof
Patent Information
- Application Number
- CN202411956221.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-28
- Publication Date
- 2025-04-01
AI Technical Summary
In existing quantum dot light emitting diodes, surface defects in the ZnO or ZnMgO electron transport layer lead to exciton quenching and carrier injection is unbalanced, affecting device efficiency and lifetime.
The ZnMgO electron transport layer is modified by halogen amine salts (such as 4-chlorophenethylamine iodide and 4-chlorophenethylamine chloride). Through the passivation of amine cations and halide ions, the interface exciton quenching is reduced, and the conduction band energy level is shifted upward, the electron injection barrier is increased, and the carrier injection equilibrium is promoted.
The radiation recombination efficiency of the quantum dot light emitting diode is significantly improved, the efficiency and operating life of the device are improved, the maximum EQE is increased by 43%, and the T50 time with an initial brightness of 100cd/m2 is increased by 106%.
Smart Images

Figure CN119744076A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of light emitting diodes, and in particular relates to a positive quantum dot light emitting diode and a preparation method thereof. Background Art
[0002] Colloidal quantum dots have attracted widespread attention due to their high luminescence efficiency, narrow line width, tunable wavelength, and low solution process cost. Thanks to these unique advantages, quantum dot light emitting diodes (QLEDs) have become the most promising display and lighting technology.
[0003] Currently, the most commonly used electron transport layer (ETL) materials in QLEDs are zinc oxide (ZnO) or Mg-doped ZnO (ZnMgO) nanoparticles (NPs). As a wide-bandgap semiconductor material, ZnO or ZnMgO has properties such as high mobility, high transparency, and tunable conductivity, which help to achieve efficient QLEDs. Now, ZnO or ZnMgO NPs are ubiquitous in all record-breaking QLED devices. Although ZnO or ZnMgO ETL is widely used and considered as the basis of high-efficiency QLED, there are some problems. On the one hand, due to surface defects in ZnO or ZnMgO, excitons are easily quenched at the QD / ZnO or ZnMgO interface through interfacial charge transfer processes and / or interstitial assisted non-radiative recombination processes, which deteriorates the device performance; on the other hand, the carrier mobility of ZnO or ZnMgO is higher than that of organic materials, and the conduction band energy level of ZnO or ZnMgO is close to that of QDs, which usually produces spontaneous or barrier-free electron injection, while there is a considerable energy barrier at the interface between QD and organic HTL, which hinders the effective injection of holes. Therefore, the efficiency of electron injection into QD EML is higher than that of hole injection, resulting in unbalanced carrier injection. Excessive electrons are injected into quantum dots, which increases the possibility of non-radiative recombination and limits the efficiency and working life of QLEDs.
[0004] To solve the above problems, a series of methods are used to promote carrier injection balance and suppress interface defects, such as inserting an insulating layer at the interface between QDs and ETL to reduce electron injection and using in-situ ion doping to reduce its mobility, adjust the band position and passivate defects to improve device performance. However, the thickness of the interfacial intercalation layer is difficult to control, resulting in difficulty in regulating device performance and complex device construction. Ion-doped ZnO or ZnMgO nanocrystals as electron transport layers will cause a more obvious efficiency roll-off of QLEDs, affecting device brightness.
[0005] Therefore, in order to promote carrier balance and improve device efficiency and life, it is urgent to develop other strategies to regulate the energy levels of ZnO or ZnMgO NPs, passivate surface defects and improve device life. Summary of the invention
[0006] One of the purposes of the present invention is to provide a positive quantum dot light-emitting diode. The present invention constructs a quantum dot light-emitting diode based on a ZnMgO electron transport layer modified with a halogen amine salt surface, reduces interface exciton quenching, improves the device's radiation recombination efficiency, and improves the efficiency and operating life of the device.
[0007] To achieve the above object, the present invention adopts the following technical solutions:
[0008] A positive quantum dot light-emitting diode, comprising, from bottom to top, an anode, a hole injection layer, a hole transport layer, a quantum dot light-emitting layer, an electron transport layer and a cathode;
[0009] The electron transport layer is a ZnMgO film modified by halogen amine salt.
[0010] Furthermore, the halogen amine salt is 4-chlorophenethyl amine halide.
[0011] Furthermore, the halogenamine salt is 4-chlorophenethylammonium iodide or 4-chlorophenethylammonium chloride.
[0012] Furthermore, the preparation process of the electron transport layer is as follows:
[0013] The halogen ammonium salt solution is added to the ZnMgO nanoparticle solution to obtain the halogen amine salt modified ZnMgO nanoparticle solution; the amine salt modified ZnMgO nanoparticle solution is spin-coated and annealed to prepare the halogen amine salt modified ZnMgO film.
[0014] Furthermore, the concentration of the ZnMgO nanoparticle solution is 20-30 mg / mL, and the concentration of the halide ammonium salt solution is 0.5-2 mg / mL.
[0015] Furthermore, the halogen ammonium salt solution accounts for 1% to 5% of the volume of the ZnMgO nanoparticle solution; the solvent of the halogen ammonium salt solution is isopropanol, and the solvent of the ZnMgO nanoparticle solution is ethanol.
[0016] Furthermore, the anode is an ITO electrode; the material of the hole transport layer is at least one of polyvinyl carbazole, poly[(9,9-dioctylfluorene-2,7-diyl)-co-(4,4′-(N-(4-sec-butylphenyl)diphenylamine)], poly[bis(4-phenyl)(4-butylphenyl)amine], tri(4-carbazolyl-9-ylphenyl)amine, 4,4′-di(9-carbazole)biphenyl, poly((9,9-dioctylfluorene-2,7-diyl)-alt-(9-(2-ethylhexyl)-carbazole-3,6-diyl)); the material of the quantum dot light-emitting layer is CdSeS / ZnSeS / ZnS quantum dots; the cathode material is any one of Al, Ag, Cu, Au, and alloy electrodes.
[0017] The second object of the present invention is to provide a method for preparing a positive quantum dot light-emitting diode. The method is simple and easy to operate, provides a way of preparing high-efficiency and long-life quantum dot light-emitting diodes, and is conducive to a deep understanding of the impact of carrier injection imbalance and non-radiative recombination on device performance.
[0018] To achieve the above object, the present invention adopts the following technical solutions:
[0019] A method for preparing a positive quantum dot light-emitting diode comprises the following steps:
[0020] (1) cleaning a glass substrate containing a transparent electrode to obtain a clean substrate;
[0021] (2) spin coating the hole injection layer solution on the clean substrate obtained in step (1), and annealing to form a hole injection layer;
[0022] (3) spin coating the hole transport layer solution on the hole injection layer and annealing to form a hole transport layer;
[0023] (4) spin coating the quantum dot light-emitting layer solution on the hole transport layer to form a quantum dot light-emitting layer;
[0024] (5) spin coating an electron transport layer solution on the quantum dot light-emitting layer, and annealing to form an electron transport layer; the electron transport layer solution is a ZnMgO nanoparticle solution modified by a halogen amine salt, and the electron transport layer is a ZnMgO thin film doped with a halogen amine salt;
[0025] (6) Vapor-depositing a metal electrode on the electron transport layer to form a cathode, thereby obtaining the positive quantum dot light-emitting diode.
[0026] Furthermore, in step (5), the annealing temperature is 50-70° C., the annealing time is 20-30 min, and the film thickness of the electron transport layer is 45-60 nm.
[0027] Furthermore, in step (2), the hole injection layer solution is a PEDOT:PSS solution; the annealing temperature is 125-130°C, the annealing time is 15-20min, and the thickness of the hole injection layer is 40-45nm; in step (3), the annealing temperature is 145-150°C, the annealing time is 30-35min, and the thickness of the hole transport layer is 35-40nm.
[0028] Furthermore, the quantum dot light-emitting layer solution in step (4) is an n-octane solution of CdSeS / ZnSeS / ZnS quantum dots; the concentration of the quantum dot light-emitting layer solution is 15-20 mg / mL, and the thickness of the quantum dot light-emitting layer is 20-30 nm.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] 1. The present invention modifies the surface of ZnMgO by halogenamine salts 4-chlorophenethylammonium iodide (Cl-PEAI) and 4-chlorophenethylammonium chloride (Cl-PEACl), thereby shifting the conduction band energy level of the ZnMgO electron transport layer upward, increasing the interface barrier between the electrode and the electron transport layer, and facilitating the blocking of excessive electron injection and promoting the injection balance of carriers in the device. In addition, the present invention uses ZnMgO as the electron transport layer of the device, which is simple to operate, has abundant raw material sources, is cheap and easy to prepare, and can effectively reduce the cost in the preparation process.
[0031] 2. The amine cations in the halogen amine salt of the present invention can passivate the hydroxyl defect states on the surface of ZnMgO. After the highly electronegative halogen ions enter the ZnMgO lattice, they passivate the oxygen vacancy defects, thereby reducing the interface exciton quenching and improving the radiation recombination efficiency of the device.
[0032] 3. The QLED device finally prepared by the present invention has a maximum EQE of 23%, which is 43% higher than the standard device (EQE of 16%), and an initial brightness of 100 cd / m 2 T 50 1035h, compared with the standard device (T 50 The operating life of the device was significantly improved by 106%. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 is a schematic diagram of the device structure;
[0034] Figure 2 XRD patterns of the electron transport layer films obtained in Example 1, Example 2 and Comparative Example 1 of the present invention;
[0035] Figure 3AFM images of the electron transport layer thin films obtained in Example 1, Example 2 and Comparative Example 1 of the present invention;
[0036] Figure 4 The XPS graphs of the electron transport layer thin films prepared in Example 1, Example 2 and Comparative Example 1 of the present invention;
[0037] Figure 5 UV-Vis spectra and UPS spectra of the electron transport layer thin films obtained in Example 1, Example 2 and Comparative Example 1 of the present invention;
[0038] Figure 6 The life spectrum of the device obtained in Example 1, Example 2 and Comparative Example 1 of the present invention;
[0039] Figure 7 The device efficiency diagram is obtained for Example 1, Example 2 and Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0040] The technical solution of the present invention is further explained below in conjunction with specific embodiments, comparative examples, test examples and drawings.
[0041] In the following examples, comparative examples and test examples, the raw materials and preparation methods used are conventional materials and techniques in the art unless otherwise specified.
[0042] In the following examples, 4-chlorophenethylammonium chloride and 4-chlorophenethylammonium iodide were purchased from J&K; the detergent was purchased from Alconox, USA, model: Liquinox; acetone and isopropanol were purchased from Scientific; chlorobenzene and toluene were purchased from Sigma-Aldrich; indium tin oxide (ITO) was purchased from Tinwell Technology Ltd; PF8Cz was purchased from Futuo Optoelectronics Technology Co., Ltd.; quantum dots (QDs) were CdSeS / ZnSeS / ZnS blue light core-shell quantum dots, which were homemade in the laboratory, and the preparation method was based on patent CN202111559871.3; ZnMgO nanoparticle solution was homemade in the laboratory; the aluminum electrode was made of a density of 2.702 g / cm 3 Aluminum particles with a boiling point of 2467°C, a melting point of 660.4°C and a purity of 99.99% were prepared by evaporation, and the aluminum particles were purchased from Kurt J.Lesker; UV-ozone cleaner, instrument model: UVO-cleaner-6, purchased from Shanghai Sibin Trading Co., Ltd., power 100W, using high-intensity UV light source, main wavelengths 185nm and 254nm; UV-curable resin was purchased from Norland, USA, specification NOA63.
[0043] The conductive atomic force microscope and Kelvin probe microscope were Dimension Icon, purchased from Bruker, USA; the X-ray diffraction analyzer was Bruker D8 Advance, purchased from Bruker, Germany; the X-ray photoelectron spectrometer was AXIS-ULTRA, purchased from Kratos, UK; the variable temperature Hall effect tester was HMS-300, purchased from Ecopia, South Korea; the digital measurement source meter was Keithley 2400; the spectroradiometer was PR-735, M-75Lens, with SD card and power adapter (AC-730-6) as standard. The heating plate was 11-100-49H, purchased from Fisher. The ultraviolet photoelectron spectrometer (ESCALAB 250XI) and the device life test system were Newport Keithley N6705B. The spin coater was WS-650MZ-23NPP / LITE, purchased from Mycro, USA.
[0044] Example 1
[0045] A positive quantum dot light-emitting diode, comprising from bottom to top an anode, a hole injection layer, a hole transport layer, a quantum dot light-emitting layer, an electron transport layer and a cathode; wherein ITO is used as the anode of the QLED device, PEDOT:PSS, PF8Cz, CdSeS / ZnSeS / ZnS blue light core-shell quantum dots, and a halogen amine salt-modified ZnMgO film are used as the hole injection layer, hole transport layer, quantum dot light-emitting layer, and electron transport layer of the QLED device, respectively, and Al is used as the cathode of the QLED device; wherein the thickness of the hole injection layer is 40 to 45 nm, the thickness of the hole transport layer is 35 to 40 nm, the thickness of the quantum dot light-emitting layer is 20 to 30 nm, the thickness of the electron transport layer ZnMgO is 45 to 60 nm, and the thickness of the top electrode is 80 to 100 nm. The structure of the QLED device of this embodiment is as follows: Figure 1 Shown: ITO / PEDOT:PSS / PF8Cz / QDs / ZnMgO / Al.
[0046] The preparation process of the halogen amine salt modified ZnMgO film is as follows:
[0047] 4-Chlorophenethylammonium iodide (Cl-PEAI) is dissolved in isopropanol and filtered with a 0.20 μm filter head to obtain a Cl-PEAI solution with a concentration of 1 mg / mL; ZnMgO nanoparticles are added to ethanol to obtain a 30 mg / mL ZnMgO nanoparticle solution; then, according to the volume ratio of Cl-PEAI solution to ZnMgO nanoparticle solution being 0.02:1, the Cl-PEAI solution is added to the ZnMgO nanoparticle solution to obtain a Cl-PEAI-modified ZnMgO nanoparticle solution, which is recorded as a Cl-PEAI-ZnMgO solution; the Cl-PEAI-ZnMgO solution is spin-coated and annealed to prepare a halogenamine salt-modified ZnMgO film.
[0048] This embodiment also provides a method for preparing the above-mentioned positive quantum dot light-emitting diode, comprising the following steps:
[0049] (1) After the ITO substrate is cleaned with a detergent, it is treated with UV-ozone for 15 minutes to improve the hydrophilicity of the substrate surface to obtain a clean ITO substrate;
[0050] (2) Filter the PEDOT:PSS solution with a 0.45 μm filter head, use a pipette to draw 150 μL of the filtered solution and spin-coat it on the clean ITO substrate obtained in step (1) at a speed of 5000 rpm, wipe the edge of the ITO substrate with a cotton swab dipped in ultrapure water until the electrode is exposed, and heat anneal at 130° C. for 15 min, and naturally cool to room temperature to form a hole injection layer, thereby obtaining an ITO / PEDOT:PSS substrate;
[0051] (3) Filter the PF8Cz solution (8 mg / mL) dissolved in chlorobenzene with a 0.20 μm filter head, use a pipette to draw 35 μL of the filtered solution and drop it on the above-mentioned ITO / PEDOT:PSS substrate, keep the substrate spin-coated at 3000 rpm for 20 seconds, remove the substrate and place it on a heating table for 30 minutes and 150°C annealing treatment, and remove the substrate after annealing, and naturally cool it to room temperature to form a hole transport layer, thereby obtaining an ITO / PEDOT:PSS / PF8Cz substrate;
[0052] (4) Dissolve CdSeS / ZnSeS / ZnS blue light core-shell quantum dots with a particle size of 10 nm in n-octane (concentration of 20 mg / mL), filter with a 0.20 μm filter head, take 35 μL of the filtered solution with a pipette, drop it on the above-mentioned ITO / PEDOT:PSS / PF8Cz substrate, and keep the substrate spin-coated at 2000 rpm for 20 seconds to form a quantum dot light-emitting layer; obtain an ITO / PEDOT:PSS / PF8Cz / QDs substrate;
[0053] (5) 35 μL of Cl-PEAI-ZnMgO solution was taken and dropped onto the above-mentioned ITO / PEDOT:PSS / PF8Cz / QDs substrate, and the substrate was spin-coated at 3000 rpm for 20 seconds. The substrate was removed and placed on a heating table for annealing at 60°C for 30 minutes. After the annealing was completed, the substrate was removed and allowed to cool naturally to room temperature to form an electron transport layer film, thereby obtaining an ITO / PEDOT:PSS / PF8Cz / QDs / Cl-PEAI-ZnMgO substrate.
[0054] (6) The spin-coated ITO / PEDOT:PSS / PF8Cz / QDs / Cl-PEAI-ZnMgO substrate was placed in a thermal evaporation coating machine. When the vacuum degree of the coating machine was lower than 5.00×10 -7 mbar conditions, the electrode Al was evaporated, and the evaporation rate was maintained After the evaporation is completed, the vacuum is broken to obtain an ITO / PEDOT:PSS / PF8Cz / QDs / Cl-PEAI-ZnMgO / Al substrate; the above-constructed device ITO / PEDOT:PSS / PF8Cz / QDs / Cl-PEAI-ZnMgO / Al is encapsulated using UV-curable resin NOA63, covered with a cover glass, and cured under UV light to obtain a QLED device with Cl-PEAI-ZnMgO as an electron transport layer, recorded as Cl-PEAI-ZnMgO.
[0055] Example 2
[0056] Example 2 provides a positive quantum dot light-emitting diode, which is different from Example 1 in that the preparation process of the halogen amine salt-modified ZnMgO film is as follows:
[0057] 4-Chlorophenethylammonium chloride (Cl-PEACl) is dissolved in isopropanol and filtered with a 0.20 μm filter head to obtain a Cl-PEACl solution with a concentration of 0.5 mg / mL. ZnMgO nanoparticles are added to ethanol to obtain a 20 mg / mL ZnMgO nanoparticle solution. Then, according to a volume ratio of the Cl-PEACl solution to the ZnMgO nanoparticle solution of 0.05:1, the Cl-PEACl solution is added to the ZnMgO nanoparticle solution to obtain a Cl-PEACl-modified ZnMgO solution, which is recorded as a Cl-PEACl-ZnMgO solution. The Cl-PEACl-ZnMgO solution is spin-coated and annealed to prepare a halogenamine salt-modified ZnMgO film.
[0058] This embodiment 2 also provides a method for preparing a positive quantum dot light-emitting diode. The specific steps are consistent with those in embodiment 1, and a Cl-PEACl-ZnMgO QLED device is prepared, which is recorded as Cl-PEACl-ZnMgO.
[0059] Comparative Example 1
[0060] Comparative Example 1 provides a positive quantum dot light-emitting diode, which differs from Example 1 in that: the preparation method of the electron transport layer is as follows: ZnMgO nanoparticles are added to ethanol to obtain an ethanol solution of ZnMgO with a concentration of 30 mg / mL, and the ethanol solution of ZnMgO is spin-coated and annealed to prepare a halogenamine salt-modified ZnMgO thin film.
[0061] This comparative example 1 also provides a method for preparing a positive quantum dot light-emitting diode, and the specific steps are consistent with those of Example 1 to prepare a standard QLED device, which is denoted as ZnMgO.
[0062] Test example
[0063] Test Example 1
[0064] XRD analysis was performed on the electron transport layer films prepared in Example 1, Example 2 and Comparative Example 1 of the present invention, and the XRD powder diffraction results were as follows: Figure 2 shown.
[0065] Depend on Figure 2 It is known that all samples show the characteristic peaks of ZnMgO in the hexagonal wurtzite crystal form, and the position of the characteristic peaks has basically not changed, indicating that surface modification of ZnMgO NPs after synthesis will not change its crystal form.
[0066] Test Example 2
[0067] Experimental Example 2 AFM analysis was performed on the electron transport layer films prepared in Example 1, Example 2 and Comparative Example 1 of the present invention, and the AFM spectra were obtained as follows: Figure 3 As shown, (a) is the AFM image of the electron transport layer film obtained in Comparative Example 1, (b) is the AFM image of the electron transport layer film obtained in Example 1, and (c) is the AFM image of the electron transport layer film obtained in Example 2.
[0068] Depend on Figure 3 (a) Figure 3 (b) Figure 3 From the AFM in (c), it can be seen that the roughness of ZnMgO modified by Example 1 (Cl-PEAI) and Example 2 (Cl-PEACl) is smaller, and the smooth interface can enhance the physical contact, which is conducive to constructing a good ohmic contact, preventing electron loss, and reducing leakage current.
[0069] Test Example 3
[0070] Experimental Example 3 XPS analysis was performed on the electron transport layer thin films obtained in Example 1, Example 2 and Comparative Example 1 of the present invention, and the XPS spectra were obtained as follows: Figure 4 As shown, (a) is the Gaussian fitting analysis of the O ls spectrum of the electron transport layer film obtained in Comparative Example 1, (b) is the Gaussian fitting analysis of the O ls spectrum of the electron transport layer film obtained in Example 1, (c) is the Gaussian fitting analysis of the O ls spectrum of the electron transport layer film obtained in Example 2, and (d) is the Gaussian fitting analysis of the lattice oxygen (O M ), oxygen vacancies (V O ) and hydroxyl oxygen (O OH ) percentage comparison chart.
[0071] Depend on Figure 4 It can be seen that the O1s fine spectrum of ZnMgO NPs can be fitted into three main peaks centered at 529.9 eV, 531.5 eV and 532.5 eV, corresponding to O M , V O and O OH Wherein O in Example 1 and Example 2 OH and V O The decrease in the ratio is due to the passivation of the amine cations and halogen ions in the amine salt, accompanied by the O M The increase in proportion.
[0072] Test Example 4
[0073] Experimental Example 4: The QLED devices prepared in Example 1, Example 2 and Comparative Example 1 of the present invention were subjected to UPS test, and the UPS spectrum was obtained as shown in FIG. Figure 5 As shown, Figure 5 (a) is the UV-Vis spectra of the electron transport layers obtained in Comparative Example 1, Example 1 and Example 2, Figure 5 (b) is the (αhν) of the electron transport layer obtained in Comparative Example 1, Example 1 and Example 2 2 Relationship diagram with energy (hν) (converted from absorption spectrum), Figure 5 (c) Figure 5 (e) and Figure 5 (g) are secondary electron cutoff edge spectra of the electron transport layer obtained in Comparative Example 1, Example 1 and Example 2, respectively. Figure 5 (d) Figure 5 (f) and Figure 5 (h) are valence band edge spectra of the electron transport layers obtained in Comparative Example 1, Example 1 and Example 2, respectively.
[0074] Depend on Figure 5It can be seen that the upward shift of the conduction band energy level of ZnMgO modified by Cl-PEAI and Cl-PEACl can increase the interfacial electron injection barrier of the ETL / Al cathode, which is beneficial to reduce the injection of electrons and thus promote the carrier balance in the device. The specific results are shown in Table 1.
[0075] Table 1
[0076]
[0077] Test Example 5
[0078] Experimental Example 5 The devices obtained in Example 1, Example 2 and Comparative Example 1 of the present invention were tested for operation stability, and the life spectrum was obtained as shown in FIG. Figure 6 And as shown in Table 2.
[0079] Table 2
[0080]
[0081] Depend on Figure 6 It can be seen that through the formula Convert the device operating life to an initial brightness of 100 cd m -2 The device operating life is , where K is a constant and n=1.5 is an acceleration factor. As shown in Table 2, the T of the ZnMgO device after Example 1 (based on Cl-PEAI modification) and Example 2 (based on Cl-PEACl modification) is 50 They are approximately 870 h and 1035 h, respectively, which are 73% and 106% higher than the device of Comparative Example 1 (standard ZnMgO) (502 h).
[0082] Test Example 6
[0083] Experimental Example 6 The performance of the devices obtained in Example 1, Example 2 and Comparative Example 1 of the present invention was tested, and the relationships between current density-voltage-brightness and current density-brightness-external quantum efficiency were as follows: Figure 7 (a) and Figure 7 (b) as shown.
[0084] From 7(a) and Figure 7(b) It can be seen that compared with Comparative Example 1, the leakage current of the QLED based on Example 1 (Cl-PEAI-ZnMgO) and Example 2 (Cl-PEACl-ZnMgO) is less than that of the standard device. The reason for the reduction in current density is that the conduction band is shifted upward, which increases the electron injection barrier and reduces the injection of electrons in the device. After surface modification, the defects of Example 1 and Example 2 are passivated, the exciton quenching is reduced, the electron injection barrier is increased, the carrier injection in the QDs is more balanced, and the radiation recombination efficiency is improved. Therefore, the efficiency and life of Example 1 (Cl-PEAI-ZnMgO) and Example 2 (Cl-PEACl-ZnMgO) are improved.
[0085] In summary, the present invention adopts the ZnMgO thin film layer modified by Cl-PEAI and Cl-PEACl interface as the electron transport layer of the device, which can effectively shift the conduction band position upward, increase the electron injection barrier, reduce the electron injection efficiency, balance the carriers, and passivate the hydroxyl defect state and oxygen vacancy defect on the ZnMgO surface, reduce exciton quenching, and improve the radiation recombination efficiency of the device.
[0086] The above are only preferred embodiments of the present invention, and are not limited to the above examples. For those skilled in the art, various changes and variations are possible under the principle of the present invention. Any modifications and improvements made should be considered within the scope of protection of the present invention.
Claims
1. A positive quantum dot light emitting diode, characterized in that: From bottom to top, it includes anode, hole injection layer, hole transport layer, quantum dot light-emitting layer, electron transport layer and cathode; The electron transport layer is a ZnMgO film modified by halogen amine salt.
2. The positive quantum dot light-emitting diode according to claim 1, characterized in that: The halogenamine salt is 4-chlorophenethylamine halide.
3. The positive quantum dot light-emitting diode according to claim 1, characterized in that: The preparation process of the electron transport layer is as follows: The halogen ammonium salt solution is added to the ZnMgO nanoparticle solution to obtain the halogen amine salt modified ZnMgO nanoparticle solution; the amine salt modified ZnMgO nanoparticle solution is spin-coated and annealed to prepare the halogen amine salt modified ZnMgO film.
4. The positive quantum dot light-emitting diode according to claim 3, characterized in that: The concentration of the ZnMgO nanoparticle solution is 20-30 mg / mL, and the concentration of the halide ammonium salt solution is 0.5-2 mg / mL.
5. The positive quantum dot light emitting diode according to claim 3, characterized in that: The halogen ammonium salt solution accounts for 1% to 5% of the volume of the ZnMgO nanoparticle solution; the solvent of the halogen ammonium salt solution is isopropanol, and the solvent of the ZnMgO nanoparticle solution is ethanol.
6. The positive quantum dot light emitting diode according to claim 1, characterized in that: The anode is an ITO electrode; the material of the hole transport layer is at least one of polyvinyl carbazole, poly[(9,9-dioctylfluorene-2,7-diyl)-co-(4,4′-(N-(4-sec-butylphenyl)diphenylamine)], poly[bis(4-phenyl)(4-butylphenyl)amine], tri(4-carbazolyl-9-ylphenyl)amine, 4,4′-di(9-carbazole)biphenyl, poly((9,9-dioctylfluorene-2,7-diyl)-alt-(9-(2-ethylhexyl)-carbazole-3,6-diyl)); the material of the quantum dot light-emitting layer is CdSeS / ZnSeS / ZnS quantum dots; the cathode material is any one of Al, Ag, Cu, Au, and alloy electrodes.
7. A method for preparing a positive quantum dot light-emitting diode according to any one of claims 1 to 6, characterized in that: The steps include: (1) cleaning a glass substrate containing a transparent electrode to obtain a clean substrate; (2) spin coating the hole injection layer solution on the clean substrate obtained in step (1), and annealing to form a hole injection layer; (3) spin coating the hole transport layer solution on the hole injection layer and annealing to form a hole transport layer; (4) spin coating the quantum dot light-emitting layer solution on the hole transport layer to form a quantum dot light-emitting layer; (5) spin coating an electron transport layer solution on the quantum dot light-emitting layer, and annealing to form an electron transport layer; the electron transport layer solution is a ZnMgO nanoparticle solution modified by a halogen amine salt, and the electron transport layer is a ZnMgO thin film doped with a halogen amine salt; (6) Vapor-depositing a metal electrode on the electron transport layer to form a cathode, thereby obtaining the positive quantum dot light-emitting diode.
8. The method for preparing a positive quantum dot light-emitting diode according to claim 7, characterized in that: In step (5), the annealing temperature is 50-70° C., the annealing time is 20-30 min, and the film thickness of the electron transport layer is 45-60 nm.
9. The method for preparing a positive quantum dot light-emitting diode according to claim 7, characterized in that: In step (2), the hole injection layer solution is a PEDOT:PSS solution; the annealing temperature is 125-130°C, the annealing time is 15-20min, and the thickness of the hole injection layer is 40-45nm; in step (3), the annealing temperature is 145-150°C, the annealing time is 30-35min, and the thickness of the hole transport layer is 35-40nm.
10. The method for preparing a positive quantum dot light-emitting diode according to claim 7, characterized in that: The quantum dot light-emitting layer solution in step (4) is an n-octane solution of CdSeS / ZnSeS / ZnS quantum dots; the concentration of the quantum dot light-emitting layer solution is 15-20 mg / mL, and the thickness of the quantum dot light-emitting layer is 20-30 nm.
Citation Information
Patent Citations
Alloyed core-shell structure quantum dot and preparation method thereof
CN114058368A
Cited By
Photoresist solution as well as preparation method and application thereof
CN120928649A
A photoresist solution, its preparation method and application
CN120928649B